A development model for asessing organization's readiness towards business intelligence systems - Anjariny, Ahmed Hassan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
Business Intelligence (BI) is computer-based application utilized to assemble, provide access to and analyze data and information about an enterprise in order to formulate better informed business decisions. Currently, organizations' are spending billions of dollars on BI projects but their failure rate is high. Many researchers tried to investigate the reason behind this failure rate. They found that one of the main reasons is that many organizations are not ready for these systems. Therefore, some studies tried to participate in solving this problem by providing some readiness factors, success factors and models to help organizations in assessing their readiness toward BI systems. But unfortunately, these readiness models and factors were developed for general organization in disregard to their geographical location which emphasizes the need for a specific model considers the culture and geography as keys in the concept. Simultaneously, due to the wide emergence of BI systems, Malaysian organizations may need an empirical study to be done on them. At the same time, it was noticed that Structural Equation Modeling (SEM), which is from the very important recent tools for model validation, was not used in the previous studies. Indeed, there is lack for a software/application that can help organizations to assess their readiness toward BI systems. Therefore, this research took opportunity of filling these needs by developing a readiness model for assessing organizations' readiness toward BI system. This model was based on the previous models and factors after validating them, by using SEM, on the Context of Malaysian Organizations (CMOs). After that, a prototype for the final model was developed to be used by organizations, as an interactive tool, to assess their readiness toward BI systems. In achieving that, many processes were considered. A comprehensive investigation was done for the related studies in this area in order to encompass and take in consideration all important Readiness Factors, which helps for conceptualization of the model. After that, the process of verifying and validating the conceptual model on CMOs tool place, by using SEM. In doing so, two round questionnaires were conducted on 235 organizations in Malaysia, which have BI concept in house, to see the point of view of Malaysian organizations regarding the BI Readiness concept. The data then was analyzed by using SEM and the conceptual model was fit and valid after avoiding the questionnaire items that were having high correlations or cross-loading. After validating the conceptual model and knowing the valid items, the development of the prototype followed in order to be used by organizations to help them in assessing their readiness toward the implementation BI systems.